(untitled) (World Bulletin of Social Sciences, 2024)
The notion of lacuna, its classification and cases of delineation in the process of intercultural communication are considered in this article. Also a special attention is paid to adequacy in translation by the example of comparing the English, Russian and Uzbek languages